Factors Affecting Purchase Interest Using Marketplace Applications: Approach Perceptions Ease Of Use And Trust - Marthanti, Amas Sari; Lahat, Mohammad Amas; Santosa, Jaka (IJOSMAS, 2022)
The marketplace application is a new technology. The presence of perceptions in the acceptance of a new technology has a great influence on a person's interest in using or not using the new technology. The success or failure of the acceptance of online shopping applications by consumers can be predicted through correlational relationships and cause-and-effect relationships, which are influenced by perceptions of ease of use and user trust in the application. This research was conducted to find out how much influence the perception of ease of use and trust in the application has on buying interest using a marketplace application. The data collection method uses a questionnaire distributed to users of the marketplace application. The data obtained were then processed by multiple regression method with SPSS software version 23.00. The results showed that there was a significant positive effect of perceived ease of use on buying interest, there was a significant positive effect of trust on buying interest, there was a positive and significant effect of perceived ease of use and trust together on buying interest.